Service Quality As A Mediating Variable Of The Influence Of Digital Marketing Variables On Customer Satisfaction - Brina Mariana; M. Yani Syafei; Umi Narimawati (UNIVED Press, 2025)
This research is a quantitative study with an explanatory approach, namely an approach that uses a number of previous studies as the main material for analyzing each hypothesis formulated in this article. The data used in this article is primary data that researchers obtained from interviews with Indomaret employees spread throughout Indonesia digitally. The data obtained were analyzed using the smart PLS 4.0 analysis tool.